Predicting the Effect of Physical Parameters on the Amplitude of the Passive Cochlear Model - Kouilily, F.; Aboulkhouatem, F. E.; El khasmi, M.; Yousfi, N.; Achtaich, N. (Revista Mexicana de Ingenieria Biomedica, 2018)
The Cochlea plays a crucial role in the hearing of mammalian species including man. The basic function of the cochlea is to map sounds of different frequencies into corresponding characteristic positions on the basilar membrane. Many disciplines meet in the study of the auditory system to understand the truth function of the cochlea. An abnormality or small perturbation in the physical parameters of the cochlea may result a malfunction in the auditory system. In this paper, we developed a mathematical model in the order to show numerically the effect of stiffness and damping on the amplitude displacement in the case of a passive cochlea with the objective to study the ear dysfunction.